Evaluation of World Bank Support for Public Sector Reform - Thomas, Vinod (World Bank, Washington, DC, 2012)
The effectiveness and efficiency of a country's public sector is vital to the success of development activities, including those the World Bank supports. Sound financial management, an efficient civil service and administrative policy, efficient and fair collection of taxes, and transparent operations that are relatively free of corruption all contribute to good delivery of public services. Although a majority of countries that borrowed to support public sector reform experienced improved performance in some dimensions, there were shortcomings in important areas and in overall coordination. The frequency of improvement was higher among International Bank for Reconstruction and Development (IBRD) borrowers than among International Development Association (IDA) borrowers. Performance usually improved for public financial management, tax administration, and transparency, but performance did not usually improve with respect to civil service. Direct measures to reduce corruption such as anticorruption laws and commissions rarely succeeded. Recommendations to the Bank focus on improving guidelines for civil service and anticorruption reforms and on setting realistic objectives and sequencing for reforms. The Bank has helped develop tools to improve transparency and reduce bureaucratic corruption, such as the Public Expenditure Tracking Survey (PETS), quantitative service delivery surveys, and the Business Environment and Enterprise Performance Survey (BEEPS).